The Progestin Revolution: progestins are arising as the dominant players in the tight interlink between contraceptives and bleeding control - Donna Shoupe (BMC, 2021)
Abstract Since the introduction of the first modern contraceptive methods, the interlink between bleeding control and contraceptive development has been a dominant and critical factor. This interplay has led to the development of safer and better contraceptive methods that are often used to control bleeding in both women with normal bleeding patterns as well as in those suffering from heavy menstrual bleeding (HMB). The success of progestin-only methods, such as hormonal IUDs or progestin dominant oral contraceptives in substantially decreasing and controlling menstrual bleeding, has led to development of multiple progestin-only protocols for the sole purpose of bleeding control. These include protocols designed to stop acute heavy bleeding as well as manage long-term bleeding. Recent publications describe a variety of protocols using high dose oral progestin pills with or without a medroxyprogesterone acetate (MPA) injection that demonstrate high effectiveness and good tolerability. Comparted to many other progestins, MPA is not converted in part into ethinyl estradiol and appears to have a progestin-only advantage. Norethindrone acetate (NET acetate) is converted in part to ethinyl estradiol and therefore is an especially good option for bleeding control in patients with low estrogen levels that would benefit from estrogen replacement (such as in premenopausal women with premature menopause or hypothalamic hypogonadism).